An update on the safety of tacrolimus in kidney transplant recipients, with a focus on tacrolimus minimization. Issue 4 (3rd April 2019) - Jouve, Thomas; Noble, Johan; Rostaing, Lionel; Malvezzi, Paolo
ABSTRACT: Introduction : Tacrolimus-based immunosuppression remains the immunosuppressive drug of choice in kidney transplantation. Areas covered : Its safety profile is closely linked to its pharmacokinetic properties. A narrow therapeutic range allows to limit under- and over-immunosuppression consequences. Minimization of tacrolimus exposure, using appropriate companion drugs, leads to the best renal outcomes in the long term. Also, reducing tacrolimus exposure variability helps in reducing tacrolimus toxicity. The novel concept of tacrolimus concentration-to-dose ratio (C/D ratio) associates with renal outcomes as well and provides some new possible improvements on tacrolimus safety, possibly by identifying kidney transplant recipient subpopulations at higher risk of tacrolimus toxicity. Similarly, the incidence of new-onset diabetes after transplantation (NODAT), a major side-effect of tacrolimus, can also be reduced by optimizing tacrolimus exposure. In this review, the authors summarize the safety profile of tacrolimus when optimizing mean tacrolimus exposure, tacrolimus exposure variability and tacrolimus C/D ratio. The impact of these adjustments on nephrotoxicity and NODAT is reviewed. Using such prescription optimization, tacrolimus' safety profile is positive. Expert opinion : Tacrolimus-based immunosuppression remains a valid option for kidney transplant recipients, and might even improve by individualizing prescriptions, the next frontier in transplant immunosuppression.